1980
DOI: 10.2527/jas1980.5151148x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Hormonal Response of Heifers to Various Photoperiods

Abstract: Body growth and dry matter intake were measured in three groups of 16 Holstein heifers exposed to (1) natural, (2) 16 hr light: 8 hr dark (16L:8D) or (3) 24L:0D photoperiods for November 11 to March 10. Average daily gain (ADG) of heifers subjected to 16L:8D was 11 (P less than .05) and 17% (P less than .02) greater than ADG of animals receiving 24L:0D or natural photoperiod, respectively. Heifers subjected to 16L:8D consumed 6.9 and 8.3% more (P less than .01) dry matter per day than did animals exposed to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
1
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(50 citation statements)
references
References 14 publications
8
40
1
1
Order By: Relevance
“…Improved growth performance with extended photoperiod has been reported for cattle exposed to light intensities greater than or equal to 104 lux (Peters et al 1980;Stanisiewski et al 1988;Zinn et al 1986a). Survey results by Reksen et al (1999) indicated that extended photoperiod using low intensity (mean = 36 lux, range = 4 to 160 lux) light increased milk production of dairy cows.…”
Section: Prolactinmentioning
confidence: 91%
See 2 more Smart Citations
“…Improved growth performance with extended photoperiod has been reported for cattle exposed to light intensities greater than or equal to 104 lux (Peters et al 1980;Stanisiewski et al 1988;Zinn et al 1986a). Survey results by Reksen et al (1999) indicated that extended photoperiod using low intensity (mean = 36 lux, range = 4 to 160 lux) light increased milk production of dairy cows.…”
Section: Prolactinmentioning
confidence: 91%
“…Why this was not the case for the evening-fed EP treatment is not known. Peters et al (1980) found that EP improved heifer growth in a cold environment without a concomitant effect on plasma PRL. Thus, the importance of the PRL response to light is under question.…”
Section: Prolactinmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,20 However, prolactin is highly variable depending on animal gender, reproductive state, 1 day length, 10 season of the year, 14,15 and temperature. 21 Therefore, a more direct diagnostic tool is needed to determine if ergot alkaloids in pasture plants are in fact ingested by the animal.…”
Section: Discussionmentioning
confidence: 99%
“…A similar feature was also noted by Ravault and Ortavant (1977) The pattern of cortisol spikes showed that the main difference between the two photoperiods was in the size of the peaks rather than in their frequency. The mean number of episodes compares closely with that observed by Fulkerson and Tang (1979) Forbes, 1982) and active immunisation against prolactin depresses growth (Ohlson et al, 1981) there has been a report of a photoperiodic effect on growth in cattle in which prolactin was very low due to low environmental temperatures (Peters et al, 1980 …”
mentioning
confidence: 60%